Synthesis and Characterization of Frustrated Spin Ladders SrFe2S2O and SrFe2Se2O. Issue 18 (27th May 2015) - Huh, Sungjoon; Prots, Yurii; Adler, Peter; Tjeng, Liu Hao; Valldor, Martin
Abstract: Chemical pressure was introduced by replacing Ba atoms with Sr atoms in the spin‐ladder compounds AEFe2 Ch2 O (AE = Ba, Sr; Ch = S, Se). Powders and small single crystals of SrFe2 S2 O and SrFe2 Se2 O were synthesized from SrO, Fe, and Ch (S, Se). X‐ray diffraction data were used to determine the crystal structures, which showed prominent magnetic ladderlike sublattices. The Mössbauer spectra of SrFe2 S2 O and SrFe2 Se2 O suggest the presence of localized divalent Fe ions in the FeCh3 O structural units (distorted e 3 t2 3 configuration, S = 2). Single sharp hyperfine patterns at 5 K indicate the formation of simple antiferromagnetic ground states. The spin‐ordering transitions ( T N ) were determined by magnetic, resistivity, and specific heat data to be 216 and 228 K for SrFe2 S2 O and SrFe2 Se2 O, respectively. At ca. 540 K, both compounds exhibit a similar broad maximum in χ ( Tχ max ). In comparison with BaFe2 S2 O and BaFe2 Se2 O, the Sr homologues have higher T χ max values, which suggest stronger intersite exchange interactions in accordance with the chemical pressure from the replacement of Sr atoms with Ba atoms. However, the lower Néel temperatures for the Sr homologues supports the idea that magnetic frustration is present, and it clearly has to be considered for this group of compounds. Abstract : SrFe2 Ch2 O (Ch = S, Se) contain ladder lattices of high‐spin Fe 2+ (d 6 ) ions that exhibit strong magnetic coupling. Geometrical frustration prevents long‐range spin order above T N = 216 (Ch = S) and 228 K (Ch = Se). The Mössbauer spectroscopy data require a more complex description because of the special local Fe coordination: a tetrahedron of one oxygen ion and three heavier chalcogenide ions.